Crinum latifolium var. latifolium L.: An addition to Mangrove Associated Flora of Maharashtra State of India with Special Reference to its Ecological Amplitude - S. Chavan2; A. B. Sabale2, M. V. Gokhale1,3,*, S. S. Shaikh2,3, N. (Journal of Phytology, 2011)
Mangrove ecosystem of Maharashtra is neglected as compared to that of on the east coast of India. An extensive floral survey is must so as to document the mangrove associated plant species from coastal Maharashtra. Present paper is a step towards this attempt. Crinum latifolium var. latifolium L. is a species of wide ecological amplitude; also growing along the mangroves as an associate in Maharashtra. In conformity to this, the present paper provides detailed habitat characteristics and association of the species.